Sosialisasi Bina Desa Wisata Kampus Merdeka Mandiri Untan ke Wisata Telok Berdiri Desa Sungai Kupah - Pamela Pamela; Sulistyarini Sulistyarini; Sri Maryuni; Agus Syahrani (Journal of Community Development, 2024)
Thematic Real Work Lectures (KKN) are community service programs for students at universities in Indonesia. The Tanjungpura University Thematic KKN which was carried out in the Kupah village area, Kubu Raya Regency is a form of synergy between UNTAN students from various study programs and village communities in solving problems faced by the village related to developing the Kupah village area as an environmental tourism destination (Ecotourism). The socialization activity was attended by 20 representatives of the Kupah village community. The activity was carried out using an educational lecture method to socialize tourism management in Kupah village involving all levels of society. The evaluation results showed that as many as 60 percent of the socialization participants already knew about tourism and had carried out tourism marketing.